Hydrogen Sulfide-Clues from Evolution and Implication for Neonatal Respiratory Diseases - Abhrajit Ganguly; Gaston Ofman; Peter F Vitiello (MDPI AG, 2021)
Reactive oxygen species (ROS) have been the focus of redox research in the realm of oxidative neonatal respiratory diseases such as bronchopulmonary dysplasia (BPD). Over the years, nitric oxide (NO) and carbon monoxide (CO) have been identified as important gaseous signaling molecules involved in modulating the redox homeostasis in the developing lung. While animal data targeting aspects of these redox pathways have been promising in treating and/or preventing experimental models of neonatal lung disease, none are particularly effective in human neonatal clinical trials. In recent years, hydrogen sulfide (H2S) has emerged as a novel gasotransmitter involved in a magnitude of cellular signaling pathways and functions. The importance of H2S signaling may lie in the fact that early life-forms evolved in a nearly anoxic, sulfur-rich environment and were dependent on H2S for energy. Recent studies have demonstrated an important role of H2S and its synthesizing enzymes in lung development, which normally takes place in a relatively hypoxic intrauterine environment. In this review, we look at clues from evolution and explore the important role that the H2S signaling pathway may play in oxidative neonatal respiratory diseases and discuss future opportunities to explore this phenomenon in the context of neonatal chronic lung disease.